Product reliability–oriented optimization design of time-between-events control chart system for high-quality manufacturing processes. (February 2020) - Chen, Zhaoxiang; He, Yihai; Cui, Jiaming; Han, Xiao; Zhao, Yixiao; Zhang, Anqi; Zhou, Di
In high-quality manufacturing processes, the yield is no more the only issue, and the quality control approach that also considers the product's actual performance gradually becomes the focus. Reliability is a critical dimension of quality, and its degradation in usage is always determined by the manufacturing quality. To mitigate the degradation of reliability, this article presents a product reliability–oriented optimization design of the time-between-events control chart system, where the quantitative impact of process quality on the product reliability is analyzed. First, critical-to-reliability process parameters are identified, and a product reliability degradation model is proposed considering the effect of process variations and defects. Second, the observed event and the used statistics are determined to prearrange the time-between-events chart system. Third, all individual time-between-events charts are systematically optimized to minimize the expected batch product reliability degradation caused by potential process shifts, where the cost and statistical performance are considered as constraints. The result of the case study shows that the proposed design can reduce 27.02% of batch product reliability degradation due to manufacturing process quality, and this model can also save the operating cost on the basis of attaining minimum reliability degradation in certain situations.